Women’s Readiness to Conduct Pap Smear Test at Primary Health Care Centers in Baghdad City: The Health Belief Model as A Theoretical Framework (Medico Legal Update, 2021)
Background: Cervical cancer is the second leading cause of cancer deaths in low and middle-incomecountries. The International Agency for Research on Cancer (IARC) gauges that the frequency of cervicaldisease will increment by 75% worldwide by 2030.Method: This descriptive correlational study was carried out to examine women’s readiness to performPap smear test. to (1) assess women’s readiness to perform Pap Smear test, (2) identify the associationbetween woman’s age, family’s socioeconomic status, gravidity, parity, abortion, and their Stages of Changefor conducting Pap Smear test, the Perceived Susceptibility to contract cervical cancer, the PerceivedSeriousness of cervical cancer, the Perceived Barriers to conduct Pap Smear test, the Perceived Benefits ofconducting Pap Smear Test, and the Health Motivation to conducting Pap Smear Test, and (3) investigate thedifferences in the Perceived Susceptibility to contract cervical cancer, the Perceived Seriousness of cervicalcancer, the Perceived Barriers to conduct Pap Smear test, the Perceived Benefits of conducting Pap SmearTest, and the Health Motivation to conducting Pap Smear Test between the groups of the Stages of Changefor conducting Pap Smear test woman’s level of education, family’s socioeconomic class, and family type.Results: The target population of this study was selected from adult, married women on social media. TheSR used a self-reported online survey for data collection. The SR prepared the online survey and publishedits link on the social media pages and groups, where the study objectives were demonstrated to study subjectsConclusion: Most of the women are precontemplators. The older the age, the greater the Susceptibilityto contracting cervical cancer and the better the family’s socioeconomic status, the greater the greaterSusceptibility to contracting cervical cancer.